Yes‐associated protein regulates the hepatoprotective effect of vitamin D receptor activation through promoting adaptive bile duct remodeling in cholestatic mice. Issue 1 (16th July 2021) - Xie, Jing; Fan, Yonggang; Jia, Rongjun; Yang, Fan; Ma, Liman; Li, Lihua
Abstract: Mounting clinical evidence has revealed that the vitamin D receptor (VDR) is associated with cholestatic liver injury, although the functions of VDR in this condition remain largely unexplored. Here, we investigated the effects of VDR activation on bile duct ligation (BDL) mice, and the underlying mechanisms were further investigated. A low‐calcemic VDR agonist, paricalcitol (PAL, 200 ng/kg), was intraperitoneally injected into BDL mice every other day for 5 days or 28 days. Liver histology, liver function indicators, cholangiocyte proliferation, fibrosis scores, and inflammation were evaluated. Mice treated with PAL were rescued from the decreased survival rate induced by BDL and liver damage was reduced. Mechanistically, PAL promoted cholangiocyte proliferation, which was likely conducive to proliferating bile duct maturation and increased branching of bile ducts. PAL treatment also increased the expression of Yes‐associated protein (YAP) and its target protein epithelial cell adhesion molecule (EpCam) and decreased the level of inactive cytoplasmic phosphorylated YAP. YAP knockdown abrogated PAL‐induced primary bile duct epithelial cell proliferation, confirmed with YAP inhibitor administration. In addition, BDL‐induced liver fibrosis and inflammatory cell infiltration were reduced by PAL treatment at both day 5 and day 28 post‐BDL. In conclusion, VDR activation mitigates cholestatic liver injury by promoting adaptive bile duct remodeling through cholangiocytic YAP upregulation. Because PAL is an approved clinical drug, it may be useful for treatment of cholestatic liver disease. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.